Effectiveness Of Saffron Stigma Infusion On Dysmenorrhea Pain In Adolescent Girls Of Bachelor Of Midwifery Universitas Nasional - Fitriyana, Eka; Putri Azzahroh; Vivi Silawati (International Health Sciences Journal, 2025)
Menstruation is a physiological change that occurs periodically in the female body and is influenced by reproductive hormones. However, not all female adolescents experience a normal menstrual cycle. Many suffer from conditions such as oligomenorrhea, polymenorrhea, or amenorrhea, and experience dysmenorrhea pain. Dysmenorrhea management can be performed through pharmacological and non-pharmacological methods, one of which is by consuming saffron stigma infusion. This study employed a quasi-experimental design with a twogroup pretest-posttest approach. The sample consisted of 60 female adolescents experiencing dysmenorrhea, divided into two groups: the treatment group, which received saffron stigma infusion, and the control group, which received warm compress therapy. Pain levels were measured using the Numeric Rating Scale (NRS). Data analysis was conducted using the Paired T-Test with SPSS 16 software. The study revealed that saffron stigma infusion was effective in reducing dysmenorrhea pain in female adolescents (p < 0.05), whereas the warm compress group did not show any significant changes. Saffron stigma infusion has been proven to be effective in reducing dysmenorrhea pain in female adolescents, while warm compress therapy does not provide a significant effect.